1988
DOI: 10.1016/0735-1097(88)90109-x
|View full text |Cite
|
Sign up to set email alerts
|

Differential effects of procainamide, lidocaine and acetylstrophanthidin on body surface potentials and epicardial conduction in dogs with chronic myocardial infarction

Abstract: Twenty-eight anesthetized mongrel dogs were studied 2 to 74 months after experimental myocardial infarction in order to examine the effects of procainamide, lidocaine and acetylstrophanthidin on conduction within the infarcted region and the way such effects relate to changes in body surface potentials and antiarrhythmic efficacy. In each animal, 100 to 200 QRS complexes in the X, Y, Z leads were signal averaged, vector summed and high pass filtered at 50 Hz. Susceptibility to ventricular arrhythmia was evalua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

1989
1989
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(5 citation statements)
references
References 26 publications
1
4
0
Order By: Relevance
“…In the present study, Procainamide prolonged fQRSd and LAS40 and attenuated RMS40, consistent with previous work in humans 22 and dogs 23 post myocardial infarction. This may have occurred secondary to the depolarization or repolarization mechanisms described above.…”
Section: Discussionsupporting
confidence: 93%
“…In the present study, Procainamide prolonged fQRSd and LAS40 and attenuated RMS40, consistent with previous work in humans 22 and dogs 23 post myocardial infarction. This may have occurred secondary to the depolarization or repolarization mechanisms described above.…”
Section: Discussionsupporting
confidence: 93%
“…Signal averaging of the ECG showed that in all untreated animals late potentials had developed, whereas in the zofenopril-treated animals no late potentials were present and signalaveraging parameters were (partly) recovered. The combination of a longer QRS duration, a decreased V-30, and a longer D-30, i.e., the presence of late potentials, has been shown to be the body surface representation of delayed conduction in partially surviving fibers in the infarct [24]. Therefore, zofenopril induces a modulation of infarct properties related to tachyarrhythmias.…”
Section: Discussionmentioning
confidence: 96%
“…The study end points were either induction of a ventricular arrhythmia lasting at least 10 PACE, Vol. 13 July 1990…”
Section: Electrophysiological Studymentioning
confidence: 99%